Síntese, caracterização e avaliação da atividade biológica de complexos de paládio(II) contendo ligante imínico - Gois, Elba Pereira De (2018)
Some transition metals are of great importance in the biological environment, since they interact directly with the biomolecules essential for the maintenance of life. One characteristic of the metals that make them so important as functional and structural components of living things is their propensity to lose electrons easily by forming ions with positive charges, which tend to be soluble in biological fluids. Many studies have considered the possible interactions of metal ions with biomolecules present in the living organism. The present work had as objective the preparation of new compounds of palladium (II), containing iminic ligands, with the intention of obtaining novel compounds that present pharmacological properties. The iminic ligand (Schiff's Base) was prepared by the reaction between the trans-cinnamaldehyde aldehyde and the amine p-aminoacetophenone (Hfafe) L1. The imine ligand obtained was complexed to palladium(II), leading to substitutions, with the aim of producing new coordination compounds of the formula [PdX2(Hfafe)2], where X = Cl (C1), N3 (C2), SCN (C3), Br (C4) and I (C5). The compounds were characterized by melting point or decomposition, solubility, molar conductivity, elemental analysis (CHN), IR spectroscopic techniques, 1H and 13C NMR, thermogravimetric TG-DTA studies, X-ray diffraction for monocrystal of C2 and calculations of DFT of L1. The compounds were used in biological tests for MCF-7 and MDA-MB-435 breast cancer cells, Leishmania ssp, in vitroexperiments of promastigotes and amastigotes L. (L.) brazilienses, antifungal in yeasts of the genus Candida spp.: C. albicans, C. tropicalis, C. krusei, C. glabrata, C. parapsilosis. The free ligand was shown to have a significant effect against biological tests comparable to those of the positive controls. However, the synthesized complexes showed better potential pharmacological agents than their precursor ligand. Among the synthesized complexes, the compounds [Pd(N3)2(Hfafe)2] deserve to be highlighted, which presented, qualitatively, activity against mammary cells, Leishmania and fungi tested.